Faktor yang Mempengaruhi Terjadinya Pernikahan Usia Dini - Wulan Angraini; Bintang Agustina Pratiwi; Henni Febriawati; Riska Yanuarti; Betri Anita; Oktarianita Oktarianita (Universitas Airlangga, 2019)
Bengkulu Tengah is one of the Regencies in Bengkulu Province with the highest number of marriages in the early age compared to the other nine regencies/cities, which amounted to 29.12 percent. This study aims to determine the factors that influence early marriage in Bengkulu Tengah District. This type of research is quantitative, the population were all married couples in January-September 2017. Sampling using Propotional Random Sampling technique with a total sample of 237 people. Data was collected using a valid and reliable questionnaire then analyzed using univariate and multivariabel analysis (Multiple Linear Regression Test). The result show that youngest age of marriage is 15 years, lowest income Rp 100,000, youngest menarche age 10 years, average knowledge score 6.19, attitude 29.43, media exposure 1.63, influence of friend 5, parental support 2.23, stigma 4.29. The factors that influence the occurrence of early marriage are knowledge, Age of Menarche, and Media (p value < 0.05). The age of Menarche is the most influential factor in the age of marriage. The younger the age of menarche, the younger the age of one's marriage. It is better for teens who have experienced menstruation to maintain their reproductive health by delaying marriage in their teens.